Zircon compositional systematics from Devonian oxidized I-type granitoids: examination of porphyry Cu fertility indices in the New Brunswick Appalachians, Canada - Yousefi, Fazilat; Lentz, David R.; McFarlane, Christopher R. M.; Walker, James A.; Thorne, Kathleen G. (Frontiers in Earth Science, 2024)
Zircon is a common, widely distributed accessory mineral in most igneous rocks and its refractory nature records magmatic evolution in terms of oxygen and U-Th-Pb isotopes, and trace-element contents all of which reflect the intrinsic physio-chemical evolution of the magmatic systems in which it crystallized. Zircon compositions can be used as an indicator of relative fertility of hypabyssal intrusions in terms Cu ± Mo ± Au porphyry mineralization. To further characterize syn- to post-collisional adakitic Devonian oxidized I-type granitoids in the New Brunswick (specifically, those with Cu ± Mo ± Au porphyry-style mineralization), LA-ICP-MS analyses (guided by µXRF-EDS mapping and SEM-BSE imaging of polished thin sections) of zircons from 13 granitoids was conducted. The zircons studied were similar in terms of their textures (homogenous cores, patchy zoning, oscillatory zoning, and some unzoned zircon); however, they have a wide range of trace- and minor-element (Hf, HREE, Y, Th, U) compositions. Specifically, Zr/Hf ranges between 24–60, whereas Th/U ranges between 0.15 and 5.37. The presence of inherited zircon affects the concentrations of Th and U, as well as other key elements. Estimated crystallization temperatures of granitoids, ranging from 737 to 899°C, were calculated via Ti-in-zircon geothermometry assuming reduced TiO2 and SiO2 activities. The calculated log fO2 values for zircons from some of these granitoids indicate a highly oxidized magmatic signature. Zr/Hf, Eu/Eu⁎, and (Eu/Eu⁎)/Y in zircon, as well as zircon (Ce/Nd)/Y are some of the best indicators of porphyry fertility. The Ce/Ce* in zircon exhibit a large range (1.1–590), with higher Ce/Ce* reflecting more metallogenically favourable oxidizing conditions. If Eu/Eu⁎ in zircon is ≥0.4 (relatively oxidized conditions), it indicates a high potential for an ore-forming porphyry Cu mineralizing system. Lower Eu contents reflect relatively reducing conditions, as Eu anomalies vary with oxygen fugacity as well, and the relative abundance of Eu2+ is higher, but does not substitute into the zircon lattice. The evidence extracted from analyzing the zircon composition within New Brunswick’s I-type granitoids indicates the fertility of these hypabyssal intrusions.